Find the solution for this system of equations.
2x − 3y = 2
x = 6y − 5
Answers
Answered by
0
Answer:
(x,y) = (3,4/3)
Step-by-step explanation:
2x - 3x = 2 --------------eqn 1
x= 6y -5 ------------------eqn 2
sub 2 in 1 -->>
2(6y - 5) - 3y = 2
12y - 10 - 3y = 2
9y = 12
y = 12/9
y= 4/3
now Y in eqn 2 -->>
x = 6(4 /3) - 5
x = 8 - 5
x =3
(x,y) = (3,4/3)
Similar questions
History,
2 months ago
Social Sciences,
2 months ago
Science,
2 months ago
English,
6 months ago
English,
6 months ago
Math,
11 months ago
Chemistry,
11 months ago
Environmental Sciences,
11 months ago